Twentieth-Century Canadian Law, Psychiatry, and Social Activism in Relation to Pedophiles and Child Sex Offenders - Smith, Justin F. (Université d'Ottawa / University of Ottawa, 2016)
The contemporary conflation of pedophiles and child sex offenders is a prevalent aspect of reporting in news and social media, as well as in government-sponsored efforts to prevent child sexual victimization. Throughout twentieth century Canada, however, legal experts, psychologists and psychiatrists, and social activists were recognizing the harmfulness of grouping individuals who may have a propensity to commit crime with those who have committed the most heinous of criminal acts. As early as 1938, Canadian legal experts suggested that criminal insanity was a myth, advocating for a divergence between legal punishment and psychiatric healthcare, but after World War 2 had enacted serious efforts targeting criminal sexual psychopathy. Successive Royal Commissions investigating sexual victimization and child abuse revealed that Canadian courts, jails, prisons, and remand services were unable to solely deal with the realities of child sexual victimization. Psychologists and psychiatrists of the American Psychological Association increasingly researched sex and sexuality, classifying pedophilia as a paraphilia using child sexual victimization as a diagnostic indicator and criterion. Gay liberation activists discussed inequalities posed between hetero- and homosexual ages of consent and, more rarely, thought about the total abolition of age of consent. Each of these discourses firmly advocated for a separation between thought and action, recognizing the pedophiles who had not and would not harm children. The historical roots of the conflation of pedophiles and child sex offenders makes an important contribution to understanding contemporary discourses on criminality, victimology, sexology, and sociology, and to the development of efforts which can more successfully reduce child sexual victimization.
Keywords: legal history; pedophilia; psychiatry; Canadian history; Royal Commissions